On \(\mathcal{I}\)-Lacunary Double Statistical Convergence of Weight \(g\) - Savas, Ekrem (Communications in Mathematics and Applications, 2017)
In this paper, our aim is to introduce new notions, namely, \(\mathcal{I}\)-statistical double convergence of weight \(g\) and \(\mathcal{I}\)-lacunary double statistical convergence of weight \(g\). We mainly investigate their relationship and also make some observations about these classes.